Reaching milestones of public regulations in marine environment : toward an integrative way of marine management [résumé] - (:unkn) unknown (My University, 2017)
Marine environmental law has been emerging in West Africa in 70's. International convention has been ratified and national law progressively developed. This communication will show the development of marine environmental law in West African countries using examples from Senegal, Mauritania and Cabo-Verde. This field of law use to be very sectorial. However, the development of integrative ways of regulations at international level impacts West African national law on marine environment. Lastly, examples of first steps toward an integrative way of regulation are underlined in West African countries.
Keywords: African Research